TITLE THE EMBODIMENT OF UBUNTU PHILOSOPHY IN FOSTERING EMPATHY AND COMPASSION IN SOCIAL WORK PRACTICE - Phoke Alpha Rakgwata; Ms Ramothwa JS (CV. RADJA PUBLIKA, 2025)
The Ubuntu philosophy, a rich African worldview that emphasizes humanity's holistic nature, interconnectedness, and communal values, has significant ramifications for social work practice, especially when it comes to developing empathy and compassion. Ubuntu, which has its roots in the African idea of